PENGEMBANGAN MULTIMEDIA INTERAKTIF ARTICULATE STORYLINE 3 BERBASIS MODEL PROBLEM BASED LEARNING PADA PEMBELARAN IPAS DI KELAS IV SEKOLAH DASAR - Witraini Tanjung, Yulia; Zuryanty; Media, Afriza; Ulya Akmal, Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research is motivated by the utilization of technology-based learning media in the field is still not optimal, especially because teachers still face obstacles in designing innovative and varied media, so that the active participation of students during the learning process is relatively low. The purpose of this study is to design interactive multimedia assisted by Articulate Storyline 3 which is based on the Problem-Based Learning (PBL) approach for science learning on biodiversity material in grade IV of elementary school, while ensuring that the resulting product meets the standards of validity, practicality, and effectiveness. The research design chosen is Research and Development (R&D) by following the five stages of the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The product trial involved 28 grade IV students of UPT SDN 20 Dadok Tunggul Hitam, while the dissemination stage reached 27 students of UPT SDN 24 Parupuk Tabing and 25 students of SD Angkasa Lanud Sutan Sjahrir. Data collection was carried out through validation instruments of material, media, and language experts; practicality questionnaires filled out by teachers and students; and pretest-posttest scores of learning outcomes. The overall product validity level reached 94%, classified as very valid. The average practicality score was 93.3% from teachers and 91.85% from students, both categorized as very practical, while the effectiveness value based on N-Gain reached an average of 0.74, which is categorized as high. Overall, these findings prove that PBL-based interactive multimedia built with Articulate Storyline 3 is suitable as a learning resource for science to improve the quality of learning biodiversity material in grade IV of elementary school.